Social and Governance Activities Towards the Process of Social Integration of Rural Multi-Ethnic Communities - Muhammad Arsyad; Jamaluddin Hos; Suharty Roslan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to uncover social and governmental activities toward the process of social integration of rural multiethnic communities by methods of collecting information through interviews and observations. The selection of informants is carried out using the snowball method that is, first of all, looking for key informants who have in-depth knowledge of the differences in social conditions, the process of social integration of farmers, then key informants who indicate other informants who know and understand the research problem. The results showed that social activities and government activities are a process of social integration in rural multiethnic societies. Social activities are manifested in the form of harmonious social relations, mutual assistance, mutual assistance in caring for public facilities, and thanksgiving party activities. In addition, social activities are manifested in managing rural independent self-help groups, where the administrators and members are representations of each ethnicity. The results of these studies contribute to realizing the social integration of multiethnic communities. Similarly contribute to the process of socio-cultural, economic, and political integration of organizations and social groups of multiethnic societies. The process of social integration of a multiethnic society means the restructuring, revitalization, and functionalization of every activity of various groups and socio-cultural, economic, and political institutions, where administrators and members are representatives of each ethnicity in society